2015
DOI: 10.17507/jltr.0606.15
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Instructional and Management Talk in English Foreign Language Classroom

Abstract: Abstract-This study was conducted to find out the contexts and frequency of instructional and management talks use and the frequency of native and target language use for instructional and management talks. The subjects of this study were four Indonesian English teachers. The data was collected by observation. The finding showed that teachers use instructional talk in 5 contexts and management talk in 15 contexts. Teachers talk more for management talk than instructional talk. Teachers used target language mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 9 publications
1
14
0
Order By: Relevance
“…The collected data from video recording were transcribed and then coded to categorize teacher talk types found and students' participation encouraged by the talk. Teacher talk types were coded using teacher talk in terms of instructional talk and management talk by Zulfah et al (2015), while students' participation types were categorized using criteria adopted from Turner and Patrick (2004) and Crosthwaite et al (2015). After the coding, the data were calculated to see the most types of teacher talk found and how students' participation types were encouraged by the teacher through the talks.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The collected data from video recording were transcribed and then coded to categorize teacher talk types found and students' participation encouraged by the talk. Teacher talk types were coded using teacher talk in terms of instructional talk and management talk by Zulfah et al (2015), while students' participation types were categorized using criteria adopted from Turner and Patrick (2004) and Crosthwaite et al (2015). After the coding, the data were calculated to see the most types of teacher talk found and how students' participation types were encouraged by the teacher through the talks.…”
Section: Methodsmentioning
confidence: 99%
“…Teacher talk categories proposed in FIAC is consist of direct influence (accept feeling, praises or encourages, accept or uses students' ideas, and ask questions) and indirect influence (lecturing, giving direction, and criticizing or justifying authority). Zulfah, Rasyid, Rahman, & Rahman, (2015) study which focused on teachers' instructional and management talk, proposed 20 contexts of teacher talk found in the classroom. The instructional talk which is the language relates to transfer teaching material consists of giving an explanation, giving directions, giving correction, asking questions, and answering questions.…”
Section: Introductionmentioning
confidence: 99%
“…(2016) where some schools in Indonesia mostly focused on the use of textbook and students' worksheets in English teaching in primary education where students were asked to answer all questions in the textbook or worksheets. Even more, Sutiah (2011) andZulfah, Rasyid, Rahman, &Rahman (2015) reported that teachers mainly used traditional teaching and management in English class.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, students' mastery of English vocabulary in some primary schools in Indonesia is considered low (See (Sutiah, 2011); (Kasman, Kaseng, Hanafie, & Daeng, 2014); and (Zulfah et al, 2015). They reported that students failed in some vocabulary tests.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation